Aspek Hukum Pidana Pada Kejahatan Perbankan Dalam Perspektif Undang Republik Indonesia Nomor 10 Tahun 1998 Tentang Perbankan - Bambang Fitrianto (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
Law No. 10 of 1998 defines a bank as a legal entity which collects funds from the public in the form of savings and distribute them to the public in the form of loans and saving/ or other forms in order to improve the standard of living. But in its development, banks increasingly show the negative side, both are the result of the actions of people in banks and people who are closely related to banks, which is detrimental not only to the wider community but also the instability of the country's economy. This research is descriptive. This study uses a type of qualitative research. This type of research is normative legal research, namely research that refers to legal norms contained in legislation, court decisions and legal norms that exist in society